Optimizing the preparation of cooked chickpea - Engsner, Julia (2020)
The demand of processing pulses (dry beans, lentil, and peas) into various foods has increased over the recent years as they are considered a sustainable and healthy food. Thus, a sustainable processing of them is equally important for the future. A sustain-able processing should be both financial, time and energy efficient for manufactures, safe and nutritious for consumers and have a low environmental impact. Hence, an optimization of the preparation of pulses is needed and constitute the main goal of this study. In this study the optimal soaking conditions (time and temperature) and cooking time of chickpea (Cicer arietinum L.) was studied and analyzed by a Circumscribed Cen-tral Composite Design (CCC), allowing estimation of two-way interactions as well as quadratic terms. The intervals studied during soaking were 60-80 °C during 50-70 min and a cooking time of 50-90 min. Application challenges were also identified by observation of a large-scale test. The results indicated that the water content and the amount of solid loss increased with increasing temperature or time. During soaking the temperature had a greater effect on the amount of solid loss than the water content. During cooking the cooking time had an even greater effect on the water content and the solid loss than the other variables studied. In the two-way interactions obtained no synergetic effect existed, meaning that changing one variable is more efficient than changing both. When per-forming the response optimization, the solid loss was set to be minimized, the water content maximized, and no core was detected. The outcome of the response optimi-zation showed an optimal condition of 80 °C during 69 min during soaking with a following cooking time of 59 min. Furthermore, application challenges were ob-served. The main challenge identified was that the temperature was hard to regulate affecting time efficiency. Thus, the obtained optimal condition was not directly ap-plicable to a larger scale. Furthermore, the conclusion of this study indicate that the cooking time is the factor needed to be limited and is efficiently reduced by increasing the soaking temperature. This will improve the time efficiency, financial and nutritional value of the final prod-uct and reduce waste within the production.